2017
DOI: 10.1007/s11103-017-0681-x
|View full text |Cite
|
Sign up to set email alerts
|

iTRAQ-based comparative proteomic analysis provides insights into somatic embryogenesis in Gossypium hirsutum L.

Abstract: Key messageiTRAQ based proteomic identified key proteins and provided new insights into the molecular mechanisms underlying somatic embryogenesis in cotton.AbstractSomatic embryogenesis, which involves cell dedifferentiation and redifferentiation, has been used as a model system for understanding molecular events of plant embryo development in vitro. In this study, we performed comparative proteomics analysis using samples of non-embryogenic callus (NEC), embryogenic callus (EC) and somatic embryo (SE) using t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 57 publications
2
34
0
Order By: Relevance
“…AAA cv. Grand Naine, and Z. mays ( Ge et al, 2017 ; Kumaravel et al, 2017 ; Zhu et al, 2018 ). Those proteins include indole-3-pyruvate monooxygenase protein YUCCA3, an enzyme of the auxin biosynthesis, in Musa spp.…”
Section: Proteins Related To Synthesis and Metabolism Of Pgrmentioning
confidence: 99%
See 2 more Smart Citations
“…AAA cv. Grand Naine, and Z. mays ( Ge et al, 2017 ; Kumaravel et al, 2017 ; Zhu et al, 2018 ). Those proteins include indole-3-pyruvate monooxygenase protein YUCCA3, an enzyme of the auxin biosynthesis, in Musa spp.…”
Section: Proteins Related To Synthesis and Metabolism Of Pgrmentioning
confidence: 99%
“…AAA cv. Grand Naine that is more abundant in EC ( Kumaravel et al, 2017 ), and an IAA-conjugate hydrolase GH3 that is more abundant in both EC and late SE stages in Z. mays and G. hirsutum ( Ge et al, 2017 ; Zhu et al, 2018 ). GH3 collectively may result in an increase in IAA ( Zhao et al, 2001 ).…”
Section: Proteins Related To Synthesis and Metabolism Of Pgrmentioning
confidence: 99%
See 1 more Smart Citation
“…The fatty acid composition rapidly changed during SE in Daucus carota [57], and Gossypium hirsutum [33]. In our study, a total of 35 fatty acid biosynthesis related genes were differently expressed during SE (Additional file 7: Extracellular protein encoding genes effect on the transition from NEC to EC It had been reported that extracellular protein germins and germin-like (GLPs), Arabinogalactan proteins (AGPs), chitinases (CHIs), lipid transfer proteins (LTPs) and glycoprotein were critical to SE, and can be served as protein marker during early SE [58].…”
Section: Functional Classification Of Degs Base On Go and Keggmentioning
confidence: 99%
“…Meanwhile, the comparative proteome analysis during SE also characterized numerous proteins that associated with SE in many plant species, such as Maize [28], Papaya [29], Cacao [30], Sugarcane [31], Musa. spp [32], and Gossypium hirsutum [33]. The transcriptome and proteome analysis of plant SE revealed several molecular regulation mechanisms of SE, and a large number of potential key factors of embryogenesis.…”
Section: Introductionmentioning
confidence: 99%